2021
DOI: 10.1016/j.omtm.2021.02.015
|View full text |Cite
|
Sign up to set email alerts
|

NaCl and KCl mediate log increase in AAV vector particles and infectious titers in a specific/timely manner with the HSV platform

Abstract: The increasing demand for adeno-associated virus (AAV) vectors, a result from the surging interest for their potential to cure human genetic diseases by gene transfer, tumbled on low-performing production systems. Innovative improvements to increase both yield and quality of the vector produced have become a priority undertaking in the field. In a previous study, we showed that adding a specific concentration of sodium chloride (NaCl) to the production medium resulted in a dramatic increase of AAV vector parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In earlier works, we and others have shown that the HSV platform generated rAAV stocks of similar or higher infectivity than transient transfection. [21][22][23]36,37 In the current work, the infectious titers reported for the PEI method were similar or higher than the ones found with the HSV method, which was a great improvement from our previous calcium phosphate transfection data. This suggest that perhaps the suspension format, combined with a different transfection reagent, is more favorable to rAAV production and potency.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In earlier works, we and others have shown that the HSV platform generated rAAV stocks of similar or higher infectivity than transient transfection. [21][22][23]36,37 In the current work, the infectious titers reported for the PEI method were similar or higher than the ones found with the HSV method, which was a great improvement from our previous calcium phosphate transfection data. This suggest that perhaps the suspension format, combined with a different transfection reagent, is more favorable to rAAV production and potency.…”
Section: Discussionsupporting
confidence: 73%
“…Previously, we had reported side-byside data comparing the calcium phosphate transfection in adherent HEK293 21 and the HSV production system in adherent or suspension-adapted HEK293. 22,23 From both studies, the HSV platform in suspension was found superior and resulted in higher yields. Paulk et al 28 recently presented a side-by-side comparison of the PEI-transfection in HEK293 platform with the Baculovirus expression system (BEV) in insect cells, and demonstrated significant differences in the post-translational modifications of the AAV capsid, the percentage of full capsids, and the virus potency.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[5][6][7] Small molecule enhancers of recombinant protein production have demonstrated efficacy in a wide variety of mammalian cell lines [3,8,9] and the addition of chemicals as diverse as sodium chloride, sodium butyrate (NaBu) and soy peptones have been shown in previous studies to improve rAAV production yields. [9][10][11] Targeting of discrete pathways involved in the replication, packaging and trafficking of viral particles by bioactive small molecule cell culture additives offers a simple and cost-effective way of increasing viral titre and reducing overall production costs.…”
Section: Introductionmentioning
confidence: 99%